Have I Done Enough?: Lin-Manuel Miranda and Hamilton's culture of generosity. (18th August 2018) - MacDonald, Laura
Abstract : As the musical Hamilton prepared to open on Broadway in August 2015, its creator and star Lin-Manuel Miranda began curating a series of #Ham4Ham shows - free, public performances outside the theatre before a lottery was held for 10 tickets. Featuring a wide range of Broadway performers, more than 100 performances were filmed by fans and uploaded to YouTube, providing free access to the high-priced, sold-out musical. One of many acts of generosity associated with the musical Hamilton, this article suggests, such a culture of generosity springs from the musical's creator, Miranda. Whether engaging intensely with fans on social media platforms such as Twitter and Tumblr, annotating his lyrics on the website Genius.com, or leading fundraising efforts for hurricane relief in Puerto Rico, Miranda's many generous acts have been well-documented by the media. His energy has generated a culture of generosity that has spread through the actors performing in the musical's multiple companies, as well as its fans. Whether actors are volunteering with underprivileged children, or fans splashing the musical's lyrics across posters at the Women's March in 2017, performing generosity in the name of Hamilton may be the greatest possible performance of allegiance to the musical's ideologies. That Miranda has formalised his culture of generosity with his own brand, Teerico, offers disciples the chance to more formally affiliate themselves with his brand of generosity (extending their performances of solidarity even further) - and monetises Miranda's generosity in sharing his mottos and mantras via t-shirts and onesies. Lead Hamilton producer, Jeffery Seller, has carefully guarded ticket sales and facilitated the subsidised attendance of school children, inspiring positive feelings towards the musical while recruiting young people to its culture. As this article will suggest, the measure of a Hamilton fan may very well be whether she has done enough to tell its story.